Commitment System Theory: The Evolving Structure of Commitments to Multiple Targets - Klein, Howard J.; Solinger, Omar N.; Duflot, Véronique (Academy of Management Review, 2022)
Employees form commitments to multiple targets, and the coordination of those multiple commitments has become a ubiquitous part of the contemporary workplace. However, commitments are still largely studied in isolation or in one-off combinations, and current commitment theory does not account for the dynamic interrelationships among multiple commitments. To address this deficiency, we propose commitment system theory (CST). We draw upon general systems theory to depict commitment systems as malleable and interconnected structures. We present the defining elements by which commitment systems can be described and studied, develop theory regarding when commitment systems will diverge or converge over time, and discuss how taking a systems perspective resolves discrepant findings in the literature. Specifically, CST advances the commitment literature by offering an alternative perspective to explain how commitments behave as parts of larger systems. Specifically, CST accounts for (a) why and when commitments have synergistic, neutral, or conflicting interrelationships; and (b) the temporal dynamics of those interrelationships as commitments develop, change, and dissipate. CST thus offers a new vocabulary and conceptual toolkit for understanding the evolving structure of commitments to multiple targets.